Hemodynamic Changes with Different Non-Invasive Respiratory Modes for Primary Respiratory Support in Preterm Neonates: A Randomized Controlled Trial (International Journal of Child Health and Nutrition, 2025)
Background: Non-invasive ventilation has improved the survival rate and treatment outcomes for preterm neonates with respiratory distress syndrome (RDS). The hemodynamic changes that occur, particularly during the weaning period, and alternate non-invasive breathing strategies are not well understood.Aim: To assess the hemodynamic changes that occur during and after non-invasive respiratory support and the comparative efficacy of nasal continuous positive airway pressure (NCPAP) and nasal high-frequency oscillatory ventilation (NHFOV) as the primary non-invasive respiratory support for preterm neonates.Methods: A randomized controlled study on 90 preterm neonates with RDS in need of non-invasive ventilation during their first 3 days of life, randomized into 3 groups: NHFOV, vapotherm, and NCPAP groups; 30 neonates for each group. Hemodynamic changes were assessed by echocardiography, pelviabdominal, and transcranial ultrasounds during and after discontinuation of the device.Results: The NHFOV group had the lowest failure rate compared to the other two groups (p < 0.05). The Vapotherm group had a considerably shorter hospital stay and duration on non-invasive ventilation, faster reach to full enteral feeding, and lower nose trauma score (p < 0.05 for all). In terms of hemodynamic changes, the NCPAP group experienced a considerably higher percentage increase in left ventricular output (LVO) compared to the other two modalities (p < 0.001).Conclusions: NHFOV had the lowest failure rate as a primary non-invasive respiratory support in preterm infants with RDS. However, the Vapotherm group showed a shorter hospital stay and duration on non-invasive respiratory support, quicker time to reach full oral feeding, and lower nasal trauma. The NCPAP group had a higher percentage of increment in LVO.